PROJECT BASED LEARNING IN TEACHING SPEAKING OF DESCRIPTIVE TEXT FOR SENIOR HIGH SCHOOL STUDENTS - Rakhmannia, Emita Dwisda (RETAIN, 2021)
The purpose of the study is to find out the use of project based learning to improve students speaking ability and their prespective toward the implementation of the method. The design of this research is in the form of qualitative data. There are 30 students of 10th grade in a senior high school in Surabaya as the subject of this study. The result of students’ speaking would e computed by ms excel and the result of students prespective toward the implementation of project based learning will be form as transcription. As a result, that use project based learning can improve students speaking ability and the result of interview shows that students shows their interest during the implementation of the method and the most important they don’t feel afraid to speak up.